Grain size etchant for ultra-low-carbon martensitic stainless steel, method for preparing the same, and method for displaying grain size
Patent Information
- Application Number
- CN202610684094.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-18
- Publication Date
- 2026-09-04
AI Technical Summary
安全性与环保问题:传统晶粒度腐蚀剂普遍采用苦味酸作为关键成分
(1)HF溶解铬氧化物钝化膜,HNO3氧化基体,实现晶界选择性侵蚀。避免晶内组织过度腐蚀,确保晶界清晰度;
Smart Images

Figure CN122689459A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallographic testing technology for metallic materials, and in particular to a grain size etchant for ultra-low carbon martensitic stainless steel, its preparation method, and its grain size display method. Background Technology
[0002] Ultra-low carbon martensitic stainless steel (carbon content ≤0.03%), as an important branch of advanced high-strength and corrosion-resistant stainless steel, significantly improves weldability and sensitivity to stress cracking by adding alloying elements such as nickel (3.5%-7%) and molybdenum (1.5%-3%), while maintaining the high strength, high hardness, and wear resistance of traditional martensitic stainless steel. This type of material is widely used in high-end equipment manufacturing fields such as hydropower, nuclear power, and oil and gas extraction, for key components such as turbine blades, supercritical rotors, and deep-sea valves. In these applications, the original austenitic grain size is a key indicator determining its mechanical properties and service reliability, because fine grains not only improve the material's strength but also simultaneously enhance its toughness.
[0003] However, due to its high content of alloying elements such as chromium, nickel, and molybdenum, it exhibits extremely strong corrosion resistance and high grain boundary energy, making it difficult for conventional etchants to clearly visualize its grain boundaries. Furthermore, the industry's requirements for the safety, efficiency, and repeatability of the testing process are increasingly stringent, while traditional methods relying on hazardous chemicals such as picric acid or complex electrolytic processes can no longer meet the practical needs of modern industrial quality control. Therefore, developing a grain size display technology that balances safety, efficiency, and accuracy is of urgent practical significance for improving material quality control and promoting the development of high-end equipment manufacturing.
[0004] Currently, the main technical challenges in grain size indication of ultra-low carbon martensitic stainless steel are as follows: Safety and environmental concerns: Traditional grain-grading etchants commonly use picric acid as a key component. Picric acid is a highly explosive and hazardous chemical, posing an explosion risk when exposed to heat, friction, or impact, and is also extremely toxic. Since 2018, China has implemented strict controls on its production and sale, leading to procurement difficulties and safety concerns for many laboratories. Furthermore, the use of highly corrosive reagents such as high-concentration hydrochloric acid also increases operational risks and the burden of waste disposal.
[0005] Poor display results: Existing alternatives often suffer from unclear grain boundary etching and low contrast. For this type of stainless steel, the difference in corrosion resistance between grain boundaries and intragranular structures is small, making it difficult for ordinary etchants to selectively etch the grain boundaries. Some methods (such as picric acid-alcohol solutions) etch martensite laths while displaying grain boundaries, resulting in severe background interference and making grain boundaries difficult to identify. While duplex stainless steel etchants (such as potassium permanganate-sulfuric acid systems) have similar compositions, they are primarily used for phase differentiation and are not ideal for grain boundary display.
[0006] Complex operation and low success rate: Some technical solutions have complicated procedures and low success rates. For example, the CN108426883B method requires the sample to be immersed in an etchant at 50-60℃ for 6-10 hours, followed by a secondary treatment with oxalic acid solution, which takes several hours in total and is prone to causing stains on the surface; although the CN110926912A method shortens the time, it requires the use of prepared samples for pre-etching and stirring, which is complicated and the results obtained by different operators have poor reproducibility.
[0007] Limited applicability: Existing corrosives are usually designed for steels with specific compositions, resulting in poor versatility. For example, corrosives designed for high-chromium (e.g., Cr17%) or copper-containing (e.g., 17-4PH) martensitic stainless steels are not effective for low-carbon, low-chromium supermartensitic stainless steels.
[0008] In view of this, the present invention is hereby proposed. Summary of the Invention
[0009] The purpose of this invention is to provide a grain size etchant for ultra-low carbon martensitic stainless steel, its preparation method, and a grain size display method. The etchant of this invention is suitable for etching metallographic samples at room temperature, with short etching time, simple operation, and good repeatability. The etching method using the novel etchant produces clearer grain boundaries in the samples compared to traditional etchant methods.
[0010] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a grain size etchant for ultra-low carbon martensitic stainless steel, comprising hydrofluoric acid, nitric acid and water, wherein the volume ratio of hydrofluoric acid, nitric acid and water is (3-6):(3-6):(88-94), and the sum of the volume ratios of the three is 100%; The volume ratio of nitric acid to hydrofluoric acid is 1:1. The mass fraction of the components of the ultra-low carbon martensitic stainless steel is as follows: C≤0.03%, Si≤0.5%, Mn≤0.5%, P≤0.02%, S≤0.005%, Cr 11.5~13.5%, Ni 4.5~6.5%, Mo 1.5~3.0%, Ti≤1.00%, V≤1.00%, N≤0.20%, with the remainder being Fe and unavoidable impurity elements.
[0011] Furthermore, the hydrofluoric acid has a mass fraction of not less than 40%; and / or, the nitric acid has a mass fraction of 65-68%; and / or, the water is deionized water or ordinary tap water.
[0012] A second aspect of the present invention provides a method for preparing a grain size etchant for ultra-low carbon martensitic stainless steel as described in the first aspect, comprising the following steps: S1. Take hydrofluoric acid, nitric acid and water according to the composition ratio of the corrosive agent; S2. Pour water into a container, slowly add nitric acid, stir until the nitric acid and water are mixed, and finally add hydrofluoric acid and stir until the mixture is even.
[0013] A third aspect of the present invention provides a method for displaying grain size, comprising the following steps: S1. Prepare the grain size etchant described in the first aspect and make metallographic samples of ultra-low carbon martensitic stainless steel. S2. Completely immerse the metallographic sample in the etchant; S3. Remove the metallographic sample from the etchant to obtain the etched metallographic sample; S4. Observe the grain boundary morphology under a metallographic microscope and rate the grain size.
[0014] Further, in step S1, the metallographic sample size is preferably 20mm×20mm×10mm; the metallographic sample preparation steps are as follows: first, the sample is successively polished with metallographic sandpaper until the surface is flat, then polished to a mirror finish, and then ultrasonically cleaned with anhydrous ethanol and dried with cold air.
[0015] Furthermore, the polishing process employs a short-pile polishing cloth and diamond spray.
[0016] Furthermore, in step S2, the temperature of the corrosive agent is 20-25°C; and the soaking time is 10-25 seconds.
[0017] Furthermore, in step S3, after the metallographic sample is removed from the etchant, it is immediately rinsed with plenty of water, then rinsed with anhydrous ethanol, and finally dried with cold air.
[0018] The grain size etchant for ultra-low carbon martensitic stainless steel, its preparation method, and its grain size display method provided by this invention have the following advantages: (1) HF dissolves the chromium oxide passivation film, while HNO3 oxidizes the substrate, achieving selective etching of grain boundaries. This avoids excessive corrosion of the intragranular structure and ensures clear grain boundaries; (2) It works rapidly at room temperature, without the need for heating or prolonged soaking, thus shortening the testing cycle and making it suitable for batch testing; (3) It contains no picric acid or other explosive components, which significantly improves safety compared to traditional picric acid solutions (such as saturated picric acid + hydrochloric acid); it reduces storage and usage risks and complies with laboratory safety regulations. (4) Reduced cost and suitable for continuous operation; Since hydrofluoric acid in the formulation of this invention can be used as a corrosion inhibitor, the activity of the etchant of this invention remains above 80% after 20 repeated uses; The grain boundaries of the sample prepared after etching are continuous and complete, and the background martensitic lath structure is not obviously visible, which significantly improves the accuracy of rating. Attached Figure Description
[0019] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0020] Figure 1 This is a grain boundary morphology image at magnification of 50 after etchant treatment provided in Embodiment 1 of the present invention; Figure 2 This is a grain boundary morphology image with a magnification of 200 after etchant treatment provided in Embodiment 1 of the present invention; Figure 3 This is a grain boundary morphology image at magnification of 50 after etchant treatment provided in Embodiment 2 of the present invention; Figure 4 This is a grain boundary morphology image with a magnification of 200 after etchant treatment provided in Embodiment 2 of the present invention; Figure 5 This is a grain boundary morphology image at magnification of 200 after etchant treatment provided in Comparative Example 1 of the present invention. Figure 6 This is a grain boundary morphology image at magnification of 200 after etchant treatment provided in Comparative Example 1 of the present invention. Figure 7 This is a grain boundary morphology image at magnification of 50 after etchant treatment provided in Comparative Example 2 of the present invention. Figure 8 This is a grain boundary morphology image at magnification of 200 after etchant treatment provided in Comparative Example 2 of the present invention. Figure 9 This is a grain boundary morphology image at magnification of 100 after etchant treatment provided in Comparative Example 3 of the present invention. Figure 10 This is a grain boundary morphology image at magnification of 500 after etchant treatment provided in Comparative Example 3 of the present invention. Figure 11 This is a grain boundary morphology image at magnification of 50 after etchant treatment provided in Comparative Example 4 of the present invention. Figure 12 This is a grain boundary morphology image at magnification of 200 after etchant treatment provided in Comparative Example 4 of the present invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. Process parameters not specifically specified in the following embodiments are generally performed under conventional conditions.
[0022] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0023] According to a first aspect of the present invention, the present invention provides a grain size etchant for ultra-low carbon martensitic stainless steel, comprising hydrofluoric acid, nitric acid and water, wherein the volume ratio of hydrofluoric acid, nitric acid and water is (3-6):(3-6):(88-94) (e.g. 3:4:93, 3:5:92, 4:4:92, 4:5:91, 5:4:91, 5:5:90), and the sum of the volume ratios of the three is 100%; The volume ratio of nitric acid to hydrofluoric acid is 1:1. The mass fraction of the composition of the ultra-low carbon martensitic stainless steel is as follows: C≤0.03%, Si≤0.5%, Mn≤0.5%, P≤0.02%, S≤0.005%, Cr 11.5~13.5%, Ni 4.5~6.5%, Mo 1.5~3.0%, Ti≤1.00%, V≤1.00%, N≤0.20%, with the remainder being Fe and unavoidable impurity elements.
[0024] As an optional embodiment of the grain size etchant for ultra-low carbon martensitic stainless steel of the present invention, the hydrofluoric acid has a mass fraction of not less than 40%; and / or, the nitric acid has a mass fraction of 65-68%; and / or, the water is deionized water or ordinary tap water.
[0025] In this invention, hydrofluoric acid (HF) with a mass fraction ≥40% serves as the main corrosive medium, effectively dissolving the chromium oxide passivation film on the stainless steel surface; nitric acid (HNO3) with a mass fraction of 65–68% serves as an oxidant, controlling the overall corrosion rate and preventing excessive reaction; and water, either deionized or ordinary tap water, serves as a solvent to dilute the acid solution and ensure a stable reaction.
[0026] In this invention, HF is used to dissolve the chromium oxide passivation film on the stainless steel surface, and HNO3 is used to oxidize the stainless steel substrate, achieving selective etching of grain boundaries. Excessive use of HF and HNO3 will cause excessive corrosion of the intragranular structure; insufficient use will result in inadequate etching of the grain boundaries, leading to unclear grain boundary visibility. This invention limits the volume ratio of nitric acid to hydrofluoric acid to 1:1, thus ensuring both effective dissolution of the chromium oxide passivation film on the stainless steel surface and complete oxidation of the substrate.
[0027] According to a second aspect of the present invention, the present invention provides a method for preparing a grain size etchant for ultra-low carbon martensitic stainless steel as described in the first aspect, comprising the following steps: S1. Take hydrofluoric acid, nitric acid and water according to the composition ratio of the corrosive agent; S2. Pour water into a container, slowly add nitric acid, and stir slowly until the nitric acid and water are mixed. Finally, add hydrofluoric acid and stir slowly until the mixture is even.
[0028] The container described in this invention can be a plastic container, such as a polyethylene bottle. During the preparation of the corrosive agent, it is strictly forbidden to pour water into the acid to prevent violent exothermic splashing.
[0029] According to a third aspect of the present invention, the present invention provides a method for displaying grain size, comprising the following steps: S1. Prepare the grain size etchant described in the first aspect and make metallographic samples of ultra-low carbon martensitic stainless steel. S2. Immerse the metallographic sample completely in the etchant; S3. Remove the metallographic sample from the etchant to obtain the etched metallographic sample; S4. Observe the grain boundary morphology under a metallographic microscope and rate the grain size.
[0030] As an optional embodiment of the grain size display method of the present invention, in step S1, the metallographic sample size is preferably 20mm×20mm×10mm; the metallographic sample preparation steps are as follows: first, the sample is polished step by step with metallographic sandpaper until the surface is flat, then polished to a mirror finish, and then ultrasonically cleaned with anhydrous ethanol and dried with cold air.
[0031] As an optional embodiment of the grain size display method of the present invention, the polishing is performed using short-pile polishing cloth and diamond spray.
[0032] The metallographic sandpaper used for progressive polishing in this invention comprises grades #400, #600, #800, and #1000.
[0033] As an optional embodiment of the grain size display method of the present invention, in step S2, the temperature of the etchant is 20-25°C; and the immersion time is 10-25 seconds.
[0034] As an optional embodiment of the grain size display method of the present invention, in step S3, after the metallographic sample is taken out of the etchant, it is immediately rinsed with a large amount of water, then rinsed with anhydrous ethanol, and finally dried with cold air.
[0035] In this invention, rinsing with plenty of water followed by rinsing with anhydrous ethanol is used to remove residual acid from the sample surface. The corrosion endpoint is determined by the sample surface color changing from bright white to silver-gray; the reaction is terminated immediately upon removal. Excessive yellowing indicates over-corrosion.
[0036] The present invention will be further described in detail below with reference to specific embodiments and comparative examples. The stainless steel material used in the embodiments and comparative examples of the present invention is the same, namely ultra-low carbon martensitic stainless steel, with the following mass fractions of its components: C 0.01%, Si 0.23%, Mn 0.43%, P 0.015%, S 0.001%, Cr 12.5%, Ni 5.4%, Mo 1.9%, Ti 0.005%, V 0.04%, N 0.012%, with the remainder being Fe and unavoidable impurity elements.
[0037] Example 1 S1. Prepare grain size etchant and make metallographic samples of ultra-low carbon martensitic stainless steel. Preparation of grain size etchant: Measure 4 ml of 40% hydrofluoric acid, 4 ml of 65-68% nitric acid, and 92 ml of deionized water; pour the water into a 250 ml plastic container, slowly add the above-mentioned nitric acid into the plastic container, and slowly stir until the nitric acid and water are mixed evenly, and finally add the above-mentioned hydrofluoric acid, and slowly stir until the mixture is evenly mixed.
[0038] Metallographic sample preparation: A metallographic sample with dimensions of 20mm × 20mm × 10mm was cut from ultra-low carbon martensitic stainless steel. The sample was polished step by step with #400, #600, #800 and #1000 metallographic sandpaper until the surface was smooth. Then, it was polished to a mirror finish (no scratches) with short-pile polishing cloth and diamond spray. The sample was ultrasonically cleaned with anhydrous ethanol and dried with cold air.
[0039] S2. Immerse the metallographic sample completely in the etchant; etch at room temperature (25°C) for about 10 seconds, during which the sample can be slightly shaken to ensure uniform contact; when the sample surface color changes from bright white to silver-gray, immediately remove it to stop the reaction.
[0040] S3. Remove the metallographic sample from the etchant to obtain the etched metallographic sample; immediately rinse the etched metallographic sample with plenty of water, and then rinse with anhydrous ethanol to remove residual acid from the surface; dry the sample with a hairdryer on a cool setting to avoid water stains.
[0041] S4. Observe the grain boundary morphology under a metallographic microscope (50×–200×) and rate the grain size according to ASTM E112 standard.
[0042] Grain boundary morphology diagram as follows Figure 1 , 2 As can be seen from the figure, the grain boundaries appear as continuous, clear dark lines (red arrows), the original austenite grains have complete morphology, and the martensite lath background is weak, making grain size rating accurate and convenient.
[0043] Example 2 The only difference between this embodiment and Embodiment 1 is that: S1. Preparation of Grain Size Etching Agent: The proportions of the grain size etchant used in preparing ultra-low carbon martensitic stainless steel metallographic samples vary. In this embodiment, 6 ml of 40% hydrofluoric acid, 6 ml of 65-68% nitric acid, and 88 ml of deionized water are measured to prepare the etchant. The grain boundary morphology diagram is shown below. Figure 3 , 4 As can be seen from the figure, the grain boundaries appear as continuous, clear dark lines (red arrows), the original austenite grains have complete morphology, and the martensite lath background is weak, making grain size rating accurate and convenient.
[0044] Comparative Example 1 The only difference between this comparative example and Example 1 is that the ratio of hydrofluoric acid to nitric acid in the etchant is 1:2. It can be 1 ml of 40% hydrofluoric acid, 2 ml of 65-68% nitric acid, and 97 ml of deionized water. S4. Observe the grain boundary morphology under a metallographic microscope (200×) and rate the grain size according to ASTM E112 standard.
[0045] Grain boundary morphology diagram as follows Figure 5 , 6 As can be seen from the figure, the grain boundaries are discontinuous and blurred, the dark lines are discontinuous, the original austenite grain outlines are incomplete, the background interference of martensite laths is obvious, the grain size rating is biased, and the results are not accurate enough.
[0046] Comparative Example 2 The only difference between this comparative example and Example 1 is that the ratio of hydrofluoric acid to nitric acid in the etchant is 1:2. It can be 2.7 ml of 40% hydrofluoric acid, 5.4 ml of 65-68% nitric acid, and 92 ml of deionized water. S4. The grain boundary morphology is observed under a metallographic microscope (50×–200×), and the grain size is rated according to ASTM E112 standard.
[0047] Grain boundary morphology such as Figure 7 , 8 As can be seen from the figure, the grain boundaries are blurred and almost indistinguishable, with no continuous and clear dark grain boundary lines. The original austenite grain morphology is severely distorted, the martensite matrix background interference is extremely strong, the grain size rating error is extremely large, and the result is extremely inaccurate.
[0048] Comparative Example 3 The only difference between this comparative example and Example 1 is the use of the conventional picric acid method to etch ultra-low carbon martensitic stainless steel. The conventional picric acid etchant is prepared by mixing 1g of picric acid, 5ml of 36% hydrochloric acid solution, and 95ml of anhydrous ethanol solution. After grinding and polishing, the sample is immersed in the etchant for 1.5 minutes, then removed, rinsed with water, and then rinsed with anhydrous ethanol solution to remove residual etchant. Finally, it is dried with cold air. The grain boundary morphology is observed under a metallographic microscope (100×–500×), and the grain size is rated according to ASTM E112 standard.
[0049] Grain boundary morphology after corrosion Figure 9 , 10 .from Figure 9 , 10 As can be seen, the grain boundaries are blurred after corrosion (red arrow), and the background interference of the martensitic lath structure (white arrow) is severe, making it difficult to grade the grain size.
[0050] Comparative Example 4 The only difference between this comparative example and Example 1 is that the etchant contains 4 ml of 40% hydrofluoric acid, 4 ml of 65-68% nitric acid, 4 ml of 36% hydrochloric acid, and 88 ml of deionized water. The grain boundary morphology was observed under a metallographic microscope (50×–200×), and the grain size was rated according to ASTM E112 standard.
[0051] Grain boundary morphology such as Figure 11 , 12 As can be seen from the figure, although the grain boundaries are identifiable, they are not continuous and clear enough, the dark lines are slightly blurred, the original austenite grain morphology is basically identifiable, the martensite lath background has some interference, and the accuracy of the grain size rating is generally not high and can only be used as a reference.
[0052] As can be seen from the grain boundary morphology diagrams of the examples and comparative examples, the etchant containing only nitric acid and hydrofluoric acid in a volume ratio of 1:1 has a better etching effect on the metallographic samples of ultra-low carbon martensitic stainless steel. After etching with the etchant, the grain boundaries of the metallographic samples of the present invention are more obvious.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A grain-size etchant for ultra-low carbon martensitic stainless steel, characterized in that, It is composed of hydrofluoric acid, nitric acid and water, wherein the volume ratio of hydrofluoric acid, nitric acid and water is (3-6):(3-6):(88-94), and the sum of the volume ratios of the three is 100%; The volume ratio of nitric acid to hydrofluoric acid is 1:
1. The mass fraction of the components of the ultra-low carbon martensitic stainless steel is as follows: C≤0.03%, Si≤0.5%, Mn≤0.5%, P≤0.02%, S≤0.005%, Cr 11.5~13.5%, Ni 4.5~6.5%, Mo 1.5~3.0%, Ti≤1.00%, V≤1.00%, N≤0.20%, with the remainder being Fe and unavoidable impurity elements.
2. The grain size etchant for ultra-low carbon martensitic stainless steel according to claim 1, characterized in that, The hydrofluoric acid has a mass fraction of not less than 40%; and / or the nitric acid has a mass fraction of 65-68%; and / or the water is deionized water or ordinary tap water.
3. A method for preparing a grain size etchant for ultra-low carbon martensitic stainless steel as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Take hydrofluoric acid, nitric acid and water according to the composition ratio of the corrosive agent; S2. Pour water into a container, slowly add nitric acid, stir until the nitric acid and water are mixed, and finally add hydrofluoric acid and stir until the mixture is even.
4. A method for displaying grain size, characterized in that, Includes the following steps: S1. Prepare the grain size etchant as described in claim 1 or 2 to make metallographic samples of ultra-low carbon martensitic stainless steel. S2. Completely immerse the metallographic sample in the etchant; S3. Remove the metallographic sample from the etchant to obtain the etched metallographic sample; S4. Observe the grain boundary morphology under a metallographic microscope and rate the grain size.
5. The grain size display method according to claim 4, characterized in that, In step S1, the metallographic sample size is preferably 20mm×20mm×10mm; the metallographic sample preparation steps are as follows: first, the sample is polished step by step with metallographic sandpaper until the surface is flat, then polished to a mirror finish, and then ultrasonically cleaned with anhydrous ethanol and dried with cold air.
6. The grain size display method according to claim 5, characterized in that, The polishing process uses short-pile polishing cloth and diamond spray.
7. The grain size display method according to claim 4, characterized in that, In step S2, the temperature of the corrosive agent is 20-25℃; the soaking time is 10-25 seconds.
8. The grain size display method according to claim 4, characterized in that, In step S3, after the metallographic sample is removed from the etchant, it is immediately rinsed with plenty of water, then rinsed with anhydrous ethanol, and finally dried with cold air.
Citation Information
Patent Citations
An etchant and etching method for duplex stainless steel
CN108426883B
Etchant manufacturing and etching method for displaying grain boundary of low-carbon super martensitic stainless steel
CN110926912A